2010
DOI: 10.1039/c0ob00058b
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of reactions in β-cyclodextrin molecular reactors: transition state recognition

Abstract: Cyclodextrins have attracted much interest in recent years because of their potential use as molecular reactors allowing organic reactions in aqueous solution. To better understand their effect on reaction mechanisms, we have carried out a computational study of a prototypical process (neutral ester hydrolysis) in a beta-cyclodextrin (beta-CD). Two models have been used for the reactor. The first and simpler one assumes that the medium can be described by a polarizable dielectric continuum. The second one take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…First, it is necessary to unravel the effect of the thermodynamic conditions both on the solubility and on the host-guest complex formation before envisagingm ore intensivea pplications of complexation. Moreover,o nce this goal is attained, the possibility of using the macromolecular cavity as am icroreactor,a sh as been achieved for similar systems in aqueous solution, [199] would be worth investigating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it is necessary to unravel the effect of the thermodynamic conditions both on the solubility and on the host-guest complex formation before envisagingm ore intensivea pplications of complexation. Moreover,o nce this goal is attained, the possibility of using the macromolecular cavity as am icroreactor,a sh as been achieved for similar systems in aqueous solution, [199] would be worth investigating.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is necessary to unravel the effect of the thermodynamic conditions both on the solubility and on the host-guest complex formation before envisagingm ore intensivea pplications of complexation. Moreover,o nce this goal is attained, the possibility of using the macromolecular cavity as am icroreactor,a sh as been achieved for similar systems in aqueous solution, [199] would be worth investigating. Supercriticalc arbon dioxide has been successfully used at the same time as ar eactant and as olvation medium for the phosphine imide reaction, allowing the replacement of organic compounds commonly used in the synthesis of ureas to avoid the use of toxic reactants such as phosgene and isocyanates.…”
Section: Discussionmentioning
confidence: 99%
“…59 Applications to mimic host-guest interactions have also been envisaged in recent years. 60,61 However, it should be kept in mind that implicit solvent models can become questionable in some cases, such as systems with strong solvent-solute interactions and strong solvent coordination of ionic species. 62 The present CBn-TCDD systems involve only nonspecic interactions between the solvent and solute, which are expected to be able to be described by implicit solvent models.…”
Section: Complexation Energies and Deformation Energiesmentioning
confidence: 99%
“…In this work, as a first step toward understanding the polymerization process of polyester initiated by CDs, we investigated the initiation reaction mechanism of δ-valerolactone (VL) ring-opening polymerization by β-CD with the 15 The transition state recognition mechanism of the ester hydrolysis reaction in a β-CD was also investigated by quantum mechanical (QM) and MD calculations. 16 Here we chose the polymerization process of VL initiated by β-CD because this combination exhibited an efficient polymerization result and was most thoroughly investigated by the experiments. 9,10 On the basis of the experimental findings, we assumed that the reactant VL has to satisfy the following three conditions for the initiation reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Ruiz-López et al reported an atomistic mechanism of how CDs can distinguish chiral molecules by quantum mechanical/molecular mechanical (QM/MM) simulations. , Lawtrakul et al investigated the behavior of included solvent molecules and host CDs by molecular dynamics (MD) simulations . The transition state recognition mechanism of the ester hydrolysis reaction in a β-CD was also investigated by quantum mechanical (QM) and MD calculations …”
Section: Introductionmentioning
confidence: 99%